Development of novel radioiodinated exendin-4 derivatives targeting GLP-1 receptor for detection of β-cell mass. (15th December 2021) - Ogawa, Yu; Kimura, Hiroyuki; Fujimoto, Hiroyuki; Kawashima, Hidekazu; Toyoda, Kentaro; Mukai, Eri; Yagi, Yusuke; Ono, Masahiro; Inagaki, Nobuya; Saji, Hideo
Graphical abstract: Abstract: In subjects with type 2 diabetes mellitus (T2DM), pancreatic β-cell mass decreases; however, it is unknown to what extent this decrease contributes to the pathophysiology of T2DM. Therefore, the development of a method for noninvasive detection of β-cell mass is underway. We previously reported that glucagon-like peptide-1 receptor (GLP-1R) is a promising target molecule for β-cell imaging. In this study, we attempted to develop a probe targeting GLP-1R for β-cell imaging using single-photon emission computed tomography (SPECT). For this purpose, we selected exendin-4 as the lead compound and radiolabeled lysine at residue 12 in exendin-4 or additional lysine at the C -terminus using [ 123 I]iodobenzoylation. To evaluate in vitro receptor specificity, binding assay was performed using dispersed mouse islet cells. Biodistribution study was performed in normal ddY mice. Ex vivo autoradiography was performed in transgenic mice expressing green fluorescent protein under control of the mouse insulin I gene promoter. Additionally, SPECT imaging was performed in normal ddY mice. The affinity of novel synthesized derivatives toward pancreatic β-cells was not affected by iodobenzoylation. The derivatives accumulated in the pancreas after intravenous administration specifically via GLP-1R expressed on the pancreatic β-cells. Extremely high signal-to-noise ratio was observed during evaluation of biodistribution of [ 123 I]IB12-Ex4. SPECT images using normal mice showed that [ 123 I]IB12-Ex4 accumulated in the pancreas with high contrast between the pancreas and background. These results indicate that [ 123 I]IB12-Ex4 for SPECT is useful for clinical applications because of its preferable kinetics in vivo .